COVID-19 and Food Safety FAQ: Is Coronavirus a Food Safety Issue? (Mandarin Chinese): FSHN20-18CMN/FS387, 5/2020 - Seymour, Natalie; Yavelak, Mary; Christian, Candice; Chapman, Ben; Danyluk, Michelle (EDIS, 2020)
This is the Mandarin Chinese translation of FSHN20-18/FS341: COVID-19 and Food Safety FAQ: Is Coronavirus a Food Safety Issue?. It provides guidance related to COVID-19 regarding food production, handling, and packaging. Written by Natalie Seymour, Mary Yavelak, Candice Christian, and Ben Chapman, and published by the UF/IFAS Food Science and Human Nutrition Department, May 2020. FSHN20-18C/FS387: COVID-19 and Food Safety FAQ: Is Coronavirus a Food Safety Issue? (Mandarin Chinese) (ufl.edu)